Practical Teaching and Learning Methods in Malaysian Islamic Education - Mohd Hilmi Rozali; Kamarul Azmi Jasmi; Muhamad Amirul Amin Mohamad Nazim; Rasidah Sahran (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The need for the right method is important in the practical teaching and learning (T&L) of Islamic education to create a positive impact in students and produce an ideal T&L. The T&L method used must be compatible with the measurement of the students so that the objectives are planned to produce maximum impact. Therefore, this article explores the T&L method that is often used by Islamic education teachers (IET) in implementing effective Islamic Education practices. The research methodology of this writing uses a qualitative study with a case study design conducted in seven secondary schools. Purposive and snowball sampling methods were used to select study participants and informants, namely seven study participants and 21 informants.Data collection through three instruments, namely interviews as core data triangulated with observation data and document analysis as supporting data.Verbatim data from interviews, observations, and analysis documents were analyzed in Nvivo20 software, finally becoming a model of Islamic education practical T&L method (MK-PAPI) after being validated by experts. The findings show that there are 11 practical T&L methods that are often practiced by IET, namely demonstrations; repetition; discussion; problem solving; simultaneously; presentation; questionnaire; memorization; collaboration; explanation or lecture; and direct application. It can be concluded that this model significantly supports the T&L process in the classroom, ultimately shaping students' personalities to consistently embody worship and virtue in their lives. With the methods outlined, it is expected to provide valuable insights and practical guidance for teachers, schools, and educational institutions in effectively preparing, planning, managing, and implementing practical T&L. This model has the potential to add substantial value to the educational journey, empowering educators and institutions to cultivate a systematic and impactful approach to T&L.